Employee satisfaction with occupational health practitioners in the Gert Sibande District in Mpumalanga - Naicker, Kavitha (My University, 2018)
Background Client satisfaction is an increasingly important concept in service delivery, especially in the health sector. Knowing whether clients are satisfied has a multi-faceted effect. Besides being a determinant of quality service and care, satisfaction encourages happy clients to return to the service/company, so that the company retains their clientele, and may attract more. Purpose The purpose of this study was to explore and describe the employees’ level of satisfaction with the occupational health practitioners (OHPs) at one of the occupational health services (OHSs) in the Gert Sibande District in the Mpumalanga Province. Objectives The purpose of this study was to: 1. ascertain the specific demographics of employees presenting at the occupational health service (OHS) 2. ascertain and describe employees’ overall satisfaction with the occupational health practitioner’s (OHP’s) consultation on their visit 3. describe employees’ levels of satisfaction with how they were managed on their visit 4. explore and describe employees’ perceptions regarding the OHS environment 5. describe the level of trust in the relationship between the employee and the OHP. Research design and method This study made use of a quantitative cross-sectional descriptive study design to measure satisfaction experienced by clients entering and using a specific occupational health service. The survey method used was based on the Patient Satisfaction with Occupational Health Physicians tool developed by Verbeek, de Boer, van der Weide et al. (2005). Data analysis Data was captured using the guidelines provided by Verbeek et al. (2005) and was analysed using the Data Analysis and Statistical Software Version 14.1 software (STATA) computer package. Descriptive and inferential statistics were used to analyse the data. Statistical assistance was provided by a biostatistician at the Health Sciences Faculty of the University of the Witwatersrand in Johannesburg. Data were presented in tables and figures. Categorical data was presented using frequencies (number of occurrences) and percentages. Main findings Participants surveyed had a mean age of 33.87, with the majority being male, while the highest education attained was at the secondary level. Although 43.4% of participants had never used the service before, the arithmetic mean of the overall satisfaction rating with the OHP service was found to be 9.06 out of 10, implying that both new and returning participants experienced a high level of satisfaction. Most subscales showed an overall mean rating of more than 4, again implying that participants were satisfied with the services rendered. Conclusion Literature reveals that limited research has been done on South African employees’ levels of satisfaction with occupational health practitioners (OHPs). For this reason the researcher decided to ascertain and describe employees’ overall level of satisfaction with OHPs, finding a high level of satisfaction amongst the participants in this study. Ultimately, employees’ satisfaction is a strong indicator of quality of care, and employees should be able to voice their opinions on the quality of care received. Recommendations The occupational health nurse practitioner (OHNP) should be encouraged to participate in research- and evidence-based practice, as well as to formulate satisfaction surveys related to the specific workplace based on the workers’ needs, in order to identify strengths and weaknesses in the service provided. Further studies should be conducted on OHP services in South Africa. These studies can take place in different industries and provinces to ascertain if the results obtained herein are generally prevalent or will be contradicted. Furthermore, alternate methods of data collection such as qualitative one-on-one interviews should be used to yield more in-depth information on the satisfaction of employees with OHSs. Keywords Employee, Occupational Health Practitioner, Satisfaction, Occupational Health Service, Survey
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Nursing Johannesburg 2018.
Keywords: Occupational Health Services